SISTEM INFORMASI ABSENSI PEGAWAI HONOR PADA BALAI PENJAMIN MUTU PENDIDIKAN PROVINSI PAPUA - Duwila, Eda Iriyanti; Lahallo, Jim; Tatuhey, Emy L (JATISI, 2023)
The Education Quality Assurance Center (BPMP) is one of the Technical Implementation Units (UPT) of the Directorate General of Primary & Secondary Education of the Ministry of Education & Culture in Papua Province. The problems that occur in BPMP are errors when entering attendance data from the fingerprint scanner into excel spreadsheets, calculating employee working time, calculating employee overtime if any, and employee attendance data that is lost or damaged due to staffing errors. For this reason, it is necessary to have a web-based Honor Employee Attendance information system. This system was built using the waterfall method with 4 stages, namely needs analysis, system design using UML (Usecase Diagram, activity diagram, and class diagram), the 3rd stage is implementation using the Php programming language and mysql as the database, while for the last stage is testing using the blackbox method. The results of this study are that honorarium employees can be absent through fingerprints and are connected to a website-based attendance information system so that the Admin can process employee data in the system, view employee attendance, process approved permit / leave requests, process employee official travel records, and create employee attendance recap reports